A Spe salvi sugere o Vaticano II? Do Continente da Esperança - Boff, Lina (Revista eclesiástica brasileira, 2008)
Commenting on Pope Benedict XVI’s last encyclical letter, Spe salvi, in the light of the Vatican II teachings, the Author emphasizes three aspects: the hope that offers a way of being and of acting in the present, projecting human attention towards a definite future, eternity; the relationship with people, with the faith community and with the entire creation that characterizes the way of being and of acting of this hope, including its individual dimension; and finally, the effort to interpret and to take to the pastoral practice the eschatological contents of the well-known novissimos, something that will stimulate the discussion of these human life realities in the horizon of hope. The Spe Salvi, starting with the Vatican II, opens the horizon of hope for all the ramifications of current eschatology.